Risk factors for postoperative avascular necrosis of the femoral head in children with developmental dysplasia of the hip - Yong, Ming; Xu, Mengqiu; Lou, Yue; Lin, Gang (Frontiers in Pediatrics, 2023)
Aim: To investigate factors associated with postoperative avascular necrosis of the femoral head (ANFH) in developmental dysplasia of the hip (DDH) patients, and if or how the associations varied among different subpopulations of age, sex and surgical method. Methods: Patients with DDH were enrolled between October 31, 2016 and July 15, 2020 in this retrospective cohort study. The average follow-up time was 21.42 ± 10.02 months. The outcome was postoperative ANFH. The main study variables were the DDH classification, Tonnis grade, International Hip Dysplasia Institute (IHDI) classification, and preoperative traction. Multivariate logistic regression was employed to assess the associations between main study variables and postoperative ANFH. Subgroup analysis was carried out based on age at reduction, sex and surgical method. Odds ratio (ORs) and 95% confidence intervals (CIs) were calculated. Results: A total of 427 children with DDH were included, with 92 (21.55%) in the ANFH group, and 335 (78.45%) in the non-ANFH group. DDH classification was positively correlated with the risk of postoperative ANFH (OR=4.14, 95%CI: 1.08-15.77, P=0.038). Children with preoperative traction had a significantly decreased risk of postoperative ANFH in contrast to those without preoperative traction (OR=0.37, 95%CI: 0.22-0.61, P<0.001). Children aged 1-3 years who received preoperative traction has a significantly reduced risk of postoperative ANFH than those who did not receive preoperative traction (OR=0.28, 95%CI: 0.15-0.51, P<0.001). For children aged >3 years, positive association was found between DDH classification and the risk of postoperative ANFH (OR=3.75, 95%CI: 1.51-9.31, P=0.004). Girls with a more severe DDH type had a significantly higher risk of postoperative ANFH (OR=3.80, 95%CI: 1.80-8.02, P<0.001). Receiving preoperative traction was associated with a significantly decreased risk of postoperative ANFH in girls (OR=0.37, 95%CI: 0.22-0.61, P<0.001). For children undergoing open reduction, DDH classification was positively associated with the risk of postoperative ANFH (OR=3.01, 95%CI: 1.65-5.50, P<0.001), and those with preoperative traction had a lower risk of postoperative ANFH compared with those without preoperative traction (OR=0.35, 95%CI: 0.20-0.61, P<0.001). Conclusion: DDH classification and preoperative traction were associated with the risk of postoperative ANFH, and these associations varied across DDH patients with different ages, sexes and surgical methods.